COMMUNITY SERVICE EDUCATION FAMILY SUPPORT BASED ON LOCAL FAMILY VALUES IN IMPROVING MATERNAL SELF-CARE SKILLS AFTER CHILDBIRTH AT HANA KASIH CLINIC - Aspiati; Ristika Julianty Singarimbun; Putri Annisa (Cattleya Darmaya Fortuna, 2024)
The postpartum period or postpartum period is a critical phase that requires significant physical and psychological adaptation. The mother's inability to adapt in this phase risks causing physical complications to mental health problems. Self-care skills are the main key to optimal recovery, where success is greatly influenced by family support. This community service activity aims to empower families as the main companions of mothers in improving postpartum self-care skills by harmonizing medical knowledge and local family values. The activity was carried out at the Hana Kasih Clinic on October 24, 2024 by an academic team from STIKes Darmo Medan, involving postpartum mothers and their family members (husbands, parents, or relatives). The methods used are direct health counseling and interactive discussions. The evaluation was carried out through a pre-test and post-test design to measure the improvement of family understanding and maternal self-care independence. The results of the activity showed an increase in family understanding of the importance of postpartum assistance and helped erode myths or erroneous taboos that can hinder maternal recovery. In conclusion, this local value-based family support education is effective in optimizing the physical and mental recovery of mothers after childbirth in a sustainable manner.